Energy Management in Buildings Using Photovoltaics - Papadopoulou, Elena; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
Although fossil fuels remain the primary global energy source, developing and expanding economies are creating an ever-widening gap between supply and demand. Efficient energy management offers a cost-effective opportunity for both industrialized and developing nations to limit the enormous financial and environmental costs associated with burning fossil fuels. The implication of photovoltaic systems in particular presents the potential for clean and sustainable electrical energy to be generated from an unrestricted source. Energy Management in Buildings Using Photovoltaics demonstrates how adopting ‘best practices’ for energy management and harvesting can reduce the need to construct new generating facilities.   Illustrated with figures, tables and photos, Energy Management in Buildings Using Photovoltaics provides an introduction and step by step instructions on designing and planning photovoltaic systems and energy policies for both residential and industrial buildings. With particular focus on the example of provided by European industry, the creation of energy efficient systems is explored including chapters on: · Zero Energy Buildings, · Photovoltaics Technology, and · Connection of the Network.   By presenting this topic from basic introduction to highly technical analysis, Energy Management in Buildings Using Photovoltaics acts a study guide for postgraduate students as well as a key point of reference for researchers and technical consultants in the field of photovoltaic systems.  .
Keywords: Renewable energy resources; Facility management; Pollution prevention; Renewable and Green Energy; Facility Management; Industrial Pollution Prevention